Glyphosate-Resistant Kochia (Kochia scoparia) in Kansas: EPSPS Gene Copy Number in Relation to Resistance Levels. Issue 3 (September 2015) - Godar, Amar S.; Stahlman, Phillip W.; Jugulam, Mithila; Dille, J. Anita
Abstract : Reports of kochia control failure with glyphosate in western Kansas increased dramatically in the years following confirmed presence of glyphosate-resistant (GR) populations in 2007. In this study, progeny from 8 of 16 geographically dispersed kochia populations in western Kansas (seed collected in 2010) were confirmed to be resistant to glyphosate by conducting whole-plant dose-response (in greenhouse and/or outdoor environments) and shikimate-accumulation assays. Additionally, the relationship between 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) gene copy number and glyphosate resistance levels was investigated. A known glyphosate-susceptible (GS) kochia population from Ellis County, Kansas was used for comparison in all studies. Based on the herbicide rate that caused 50% reduction in biomass compared to untreated control (GR50 ) values, the 8 GR kochia populations were 4 to 11 times more resistant to glyphosate compared to the GS population. The GR50 values of kochia populations were 1.58 to 1.85 times higher under an outdoor environment compared to when grown in the greenhouse. Glyphosate-treated leaf discs of the GS kochia plants accumulated consistently higher amounts of shikimate than those of the GR plants. Additionally, the GR plants with higher levels of resistance to glyphosate had higher EPSPS : acetolactate synthase (ALS) relative gene copy number compared to those with low levels of resistance.